SARS-CoV-2 Envelope (E) Protein Binds and Activates TLR2 Pathway: A Novel Molecular Target for COVID-19 Interventions - Rémi Planès; Jean-Baptiste Bert; Sofiane Tairi; Lbachir BenMohamed; Elmostafa Bahraoui (2022)
This paper presents a molecular characterization of the interaction between the SARS-CoV-2 envelope (E) protein and TLR2. We demonstrated that the E protein, both as a recombinant soluble protein and as a native membrane protein associated with SARS-CoV-2 viral particles, interacts physically with the TLR2 receptor in a specific and dose-dependent manner. Furthermore, we showed that the specific interaction with the TLR2 pathway activates the NF-κB transcription factor and stimulates the production of the CXCL8 inflammatory chemokine. In agreement with the importance of NF-κB in the TLR signaling pathway, we showed that the chemical inhibition of this transcription factor leads to significant inhibition of CXCL8 production, while the blockade of the P38 and ERK1/2 MAP kinases only results in partial CXCL8 inhibition. Overall, our findings propose the envelope (E) protein as a novel molecular target for COVID-19 interventions: either (i) by exploring the therapeutic effect of anti-E blocking/neutralizing antibodies in symptomatic COVID-19 patients, or (ii) as a promising non-spike SARS-CoV-2 antigen candidate for inclusion in the development of next-generation prophylactic vaccines against COVID-19 infection and disease.